Risk Factors of Recurrence and Malignant Transformation of Sinonasal Inverted Papilloma - Gamrot-Wrzoł, Marta (Biomed Res Int, 2017)
Sinonasal inverted papilloma is a relatively rare disease; however, it is prevalent enough for every ENT practitioner to encounter it several times throughout medical routines. Despite the developments in experimental and clinical medicine as well as surgical techniques, our knowledge of this disease is still inadequate. With improved imaging and better diagnostic techniques, proper diagnosis and qualification for surgical approaches leave no doubt. Although the endoscopic approach seems to be the gold standard for such condition, some cases may additionally require an external approach. Regardless of the type of surgery, postoperative management is crucial for both healing and long-term follow-up. Unfortunately, the procedures are still lacking in explicit and standardized postoperative management guidelines. Moreover, an important issue is still the need for a biomarker indicative of inverted papilloma and its malignant transformation. Several particles, within the spotlight of the researchers, have been SCCA, Ki-67, Bcl-2, Wnt proteins, and many more. Nevertheless, the topic requires further investigations.